Investigating IEEE 802.15.4 for wireless body sensor network: The performance evaluation - Ali, Rabei Raad (2012)
Wireless body sensor networks (WBSN) are a specially type of wireless sensor networks (WSN) have gained in recent years thanks to the development of innovative wearable, wireless and implantable biosensors tremendous international interest. The applications of WBSN extend from intervention to everyday healthcare and in-vivo monitoring and, also fitness, sport and security. This study provides a brief introduction to the 802.15.4 standard and investigates its use in WBSNs. WBSN applications require high reliability in data transfer, but I is not dense enough to ensure there is enough redundancy in the deployment of sensors to avoid the use of the confirmation messages reaching the level of the MAC. The simulation design in this project is focused on determining the performance of the Contention Access Period (CAP) protocol of the IEEE 802.15.4 standard in WBSN by employed to predict latency, energy consumption and throughput. As well as, the simulation is executed based on Markov chain under MATLAB tool environment. However, the simulation result shows how the energy consumption in WBSN networks experiences a high path loss, this uncovers one of the main problems of using IEEE 802.15.4 in a human body environment, that is the hidden node problem, which have a significant impact on the performance WBSN, both in terms of productivity and energy consumption that cant solved without increasing the transmitted power.